Caracterização da microfísica das nuvens sobrea a Amazônia Brasileira em regiões de pasto e floresta por medidas in situ com avião instrumentado e sua aplicação direta no modelo regional RAMS - Santos, Antônio Carlos Santana dos (2005)
Improving or knowledge on cloud microphysics is fundamental to understand the clouds dynamics, its role in the atmospheric general circulation and energy balance, as well as in weather and climate prediction applications using large-scale and mesoscale models. This work aims to verify the dynamic and microphysical behavior of clouds over the Amazon basin and, in particular, to compare those behaviors over pasture and forest areas in Rondônia State. Several thermodynamic and microphysics measurements obtained in situ with the University of North Dakota instrumented aircraft (Citation II) were analyzed, allowing us to reach some conclusions about the microphysical and dynamical characteristics of clouds over pasture and forest areas. Cloud-resolving simulations using RAMS model (Regional Atmospheric Model System) were performed in order to assess sensitivities regarding vegetation cover (pasture or forest). The simulations did not show significant differences in the average vertical profiles of cloud microphysics variables (such as mixing rations for the different hydrometeor species). On the other hand, simulations using different model setups (changes in initialization or average diameter or droplets concentration), produced significant differences in precipitation and hydrometeor concentration, per exempe. Finally, simulations in which the droplets concentrations were specified showed better agreement with observations obtained during ABRACOS experiment (Anglo-Brazilian Amazonian Climate Observation Study), than simulations in which average diameter were specified.